SOME MACROECONOMIC DETERMINANTS OF INVESTORS BEHAVIOR CASE STUDY: TREASURY SECURITIES MARKET IN ALBANIA - Vanina Kalemi Jakupi (European Scientific Journal, ESJ, 2014)
This article investigates the macroeconomic determinants of the treasury securities investors using time series data. The paper examines which are the key factors influencing the investors behavior of treasury instruments by using annual data for Albania market. This study aims to analyses the relationship between the participation of the investors and some macroeconomic variables: cover ratio, debt holders ratio, core interest rate and treasury securities interest rates, weighted average maturity, general debt strategy ect. Results show that not only the financial investors but also the individual investors are very sensitive to this macroeconomic indicators. Catering to the needs of retail investors is often an essential part of the overall strategy to develop a more diversified investor base for government securities (Khan, 2013). Thus, the findings of this study can help managers and academics to build wealthy strategy to ensure a diversify investor base, one of the main objectives of the public debt management.